2005
DOI: 10.1016/j.pec.2004.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of snoezelen, integrated in 24h dementia care, on nurse–patient communication during morning care

Abstract: Objective: To investigate the effectiveness of snoezelen, integrated in 24-hour care, on the communication of Certified Nursing Assistants (CNAs) and demented nursing home residents during morning care. Methods: A quasi-experimental pre-and post-test design was conducted, comparing sic psychogeriatric wards, that implemented snoezelen, to six control wards, that continued in giving usual care. Measurements were performed at baseline and 18 months after a training 'snoezelen for caregivers'. Independent assesso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
144
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(147 citation statements)
references
References 42 publications
1
144
0
2
Order By: Relevance
“…[41][42][43][44][45] We found that RIAS was suited to capture the general content and process of hospice encounters. However, these encounters provide some unique challenges compared to traditional applications of RIAS (e.g., primary care, hospital, and clinic settings).…”
Section: Rias Application To Hospice Encountersmentioning
confidence: 99%
“…[41][42][43][44][45] We found that RIAS was suited to capture the general content and process of hospice encounters. However, these encounters provide some unique challenges compared to traditional applications of RIAS (e.g., primary care, hospital, and clinic settings).…”
Section: Rias Application To Hospice Encountersmentioning
confidence: 99%
“…It has been recommended that, in the middle to late stages of the disease, the activities should focus on fine-and gross-motor and sensory activities 2,7,10 . Consistent with this recommendation, there are currently two main approaches with promising results in people with moderate to severe dementia: Multisensory Stimulation and Motor Stimulation [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 88%
“…Observers were trained to use the software previously to video-recording analyzes. This methodology was used in previous studies with people with dementia to reduce observation bias with good reliability results 12,14 .…”
Section: Analysis Of the Video-recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the topics of EACH committee members' most recent publications, new areas of interest include, for instance, the role of the broader context in which a problem is presented [11], unconventional outcome measures such as skin conductance and cortisol [12] and new interaction analysis systems, such as sequence analysis and cue-responding [13][14][15][16][17][18]. There also appears to be an increasing interest in the role of the nurse-patient communication [19,20] and role delineation [21,22] as well as a renewed interest in decision-making [23], breaking bad news [24,25], training effects [26][27][28] and somatization [29,30]. In addition, since 2001, a number of new assessment and observation instruments have been developed [31,32] and existing ones have been (re)validated [33,34] or re-evaluated [35,36].…”
Section: Developments In Communication In Healthcarementioning
confidence: 99%